Determination and regulation of body composition in elite athletes - Sonksen, P. (British Journal of Sports Medicine, 2018)
In 2011, the International Association of Athletics Federations (IAAF) and IOC introduced a `hyperandrogenism` rule that excluded women with a serum testosterone >10 nmol/L from participating in elite sport. This rule was based on the false premise that the greater lean body mass in men was a consequence of their higher serum testosterone. This rule did not have scientific backing and the Court of Arbitration for Sport subsequently rescinded the rule following an appeal from an Indian athlete barred from the Commonwealth Games. This review covers the scientific knowledge about the development and regulation of body composition in humans but also considers the lessons learnt from evolution and breeding in animals. The importance of heredity has been documented in family and twin studies. The roles of growth hormone and sex steroids are reviewed. The Androgen Insensitivity Syndrome (AIS) is considered as a model of the role of testosterone in development of body composition and also as evidence of the importance of other factors carried on the Y-chromosome that are of prime importance but have been systematically ignored. Finally the key factors determining body composition are considered and placed in a suggested order of importance.